Cybersecurity as a Pillar of Data Protection in the Digital Era: Strategies, Regulations, and Implementation in Facing Cyber Threats - Harson Kapoh; Sabian Saleh Katijo; Khrisna Suwartono Putra; Raisya Wulandari Nurhamidin; Sintikhe Ranteallo (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Digital Transformation has changed the way people work, interact, and carry out daily activities. This revolution has brought high efficiency to communication, commerce, education, and even public services. Data is now considered “the new oil” due to its vital role in decision-making, business strategy, and the development of artificial intelligence–based technologies. However, as the use of digital technology increases, cyber threats have also grown more complex. Attacks such as malware, ransomware, phishing, identity theft, and data breaches have become global issues that can disrupt economic stability, damage an organization’s reputation, and even threaten national sovereignty. This study aims to analyze the role of cybersecurity as a pillar of data protection in the digital era. The method used is a literature review that examines various scientific publications, international standards, security reports, and regulations applicable at both national and global levels. The results show that data protection cannot rely solely on advanced technology; it also requires clear regulations, competent professionals, and public awareness of the importance of information security.